Electricity retail price in competitive marker using the risk adjusted capital asset pricing model (CAPM): a case of Thailand - Pasapong Gamonwet; Marpaung, Charles O.P.; Salam, Abdul P.; Singh, Jai Govind; PEA; Asian Institute of Technology Education Cooperation Project (Pathum Thani, Thailand : Asian Institute of Technology, 2011)
Opening access in electricity retail sector helps to promote the efficiency of electricity demand. Beside, competitive environment in electricity retail sector will also provides the chance for the customers, especially residential sector, to select preferred and affordable electricity price provided by different retailer companies . However, due to the variation of Market Clearing Price (MCP) each hour in the power supply market there is a hardly avoid able risk associated with financial return for the Electricity Retail Company. The overall objective for this study is to determine and perform preliminary analysis of an efficient electricity retail price in competitive market by using quantitative methods. Capital Asset Pricing Model (CAPM) is used for the financial analysis. In addition, risk factor has been considered by using Risk Adjustment Recovery on Capital (RAROC). The CAPM will give the price that provides the most return for the company, while RAROC will determine on what price the company has to bear the high investment recovery risk. The study generates the MCP, which is based on the equalization between electricity supply and electricity demand curves in the power pool, for 336 hours. In this study, the electricity retail price considered for the analysis purpose are in the range of 22 {u2013} 30 $/MWh. According to the using of CAPM and RAROC, the study reveals that the retailer company is expected to make highest return to the investment at the retail price of 24 $/MWh and is expected to bear highest risk of loss at the retail price of 25 $/MWh.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Energy
Thesis (M.Sc.) - Asian Institute of Technology, 2011
Keywords: Electric utilities -- Rates -- Thailand